Influence of the timing of the harvest of primary grass growth on herbage quality and subsequent digestion and performance in the ruminant animal - Rinne, Marketta (Helsingin yliopisto, Kotieläintieteen laitos, 2000)
Abstract This thesis consists of experiments in which the timing of harvest in the primary growth of grass was used to manipulate forage quality. The objectives of this work were to qualify and quantify the effects of timing of harvest of temperate forage grass species in primary growth on ruminant digestion and production. The emphasis was placed on the nutritional quality of forages, ability of different experimental techniques and measuremens to detect differences between forages, effects on ruminant digestive processes, feed intake, and finally milk production with special reference to the interactions between forage quality and concentrate supplementation. In the first experiment (publications I and II) four silages were harvested a h of timothy-meadow fescue. The D-value of ensiled herbage decreaselinear manner with advances in herbage mmaturity (750, 746, 681 and 654 g/kg DM in the order of harvest date). The silages were fed to four ruminally and duodenally cannulated young cattle at a restricted level of feed intake to allow comparisons at equal levels of DM intake. Ruminal pH was lower, ammonia concentration higher, and the molar proportion of acetate increased, propionate remained stable and butyrate decreased with increasing maturity of ensiled grass. The markedly higher intake of N when earlier cut silages were fed resulted in only minor and non-significant increases in the flow of non-ammonia-N into the duodenum. The experiment included comparisons of methods for the measurement of digesta kinetics and although remarkable between-method differences were observed, they all revealed that changes in forage quality clearly affected digestive processes. The rate of NDF digestion decreased while the rate of passage increased with a concomitant increase in the pool size of NDF in the rumen. In the second experiment (publication III), four silages were produced with D-M in the order of harvest date, and fed ad libitum to ruminally fis cows. Again differences similar to those in the ffirst experiment were found in rumen fermentation parameters, rates of NDF digestion, passage and rumen fill. These responses were also reflected in feed intake and milk production even though cows were in late lactation. The observation that increased feed intake of the early-cut silages was accompanied by decreased rumen fill suggests that the regulation of feed intake was not exclusively related to this parameter. The same feeds as used in experiment 2 were used in the third experiment (publintact dairy cows. The cows increased their energy corrected milk production by 0.50 kg and silage DM intake by 0.162 kg per 10 g/kg DM increase in D--value. The silages were supplemented with 7 or 10 kg of concentrate which contained 0 or 1.15 kg rapeseed meal. No interactions between silage harvest date and concentrate supplementation were found revealing that the possibility to compensate for poor silage quality with concentrate feeding is limited. In the fourth experiment (publication V) the effects of the timing of primary d and quality of organically grown mixed leys was studied both in primary growth and subsequent regrowth over two years. Delaying the harvest of the primary growth increased DM yield but decreased herbage digestibility. Reciprocal effects in the regrowth partly compensated for these changes but the pattern found in primary growth was still discernible in weighted herbage yields over both harvests. In conclusion, timing of the harvesting of primary growth clearly affected foaequently digestion and animal performance of ruminnants. Rapid but sometimes markedly curvi-linear decrease in forage D-value with advances in primary grass growth emphasizes the importance of the correct harvesting date. The impact of different harvesting strategies across the entire growing season remains unclear, and further research is required.
Keywords: Ko; korjuuaikapalvelu; märehtijät; nurmirehut; sulavuus; rehut; ruokinta; korjuuaste